HYDROTHERMAL LIQUEFACTION OF MAHOGANY (Swietenia macrophylla) SAWDUST (Universitas Negeri Semarang, 2018)
Hydrothermal treatment is one of the thermochemical methods to convert complex organic compounds, such as organic waste and biomass, into upgraded solid, bio-oil, and other dissolved chemicals by utilizing the properties of water at near critical condition. Such method is very potential since the process is environmentally friendly and the products have more added values. In this research, conversion of mahogany sawdust (Swietenia macrophylla) using hydrothermal treatment method was studied. The experiments were conducted in a batch autoclave with temperature range of 200-300oC and initial pressure of 1 MPa. At targeted temperature, the process was hold for 30 minutes. In addition, biomass-water ratio (B/W ratio) for experiments was varied at 1:20, 2:20 and 3:20. The liquid products, which were characterized by Gas chromatography-Mass spectrometry (GC/MS) instrument, showed the presence of furfural and several organic acids, but no flavonoid compounds. Thus, coloring potential test of hydrothermal liquid was unsuccessful; there were not any color attached on the cloth specimen. On the other hand, proximate and ultimate test results indicated that solid products had high heating value (HHV) of 4625.34-4876.25 cal/g which were comparable to that of sub-bituminous coal.